Room Monitoring Uses ESP-12E Based DHT22 and BH1750 Sensors - I Gusti Made Ngurah Desnanjaya; A A Gede Bagus Ariana; I Made Aditya Nugraha; I Komang Arya Ganda Wiguna; I Made Urip Sumaharja (Journal of Robotics and Control (JRC), 2022)
Comfortable room is one of the services that must be provided by STMIK STIKOM Indonesia campus to students. This research designed a room monitoring tool based on ESP-12E in STMIK STIKOM Indonesia. The room monitor is designed using a DHT22 sensor to measure temperature and humidity and the BH1750 sensor to measure light intensity. The tool also includes features a 16x2 I2C LCD to display measurement results. Testing is done by testing the layout circuit on the PCB and observing the measurement of temperature, humidity, and light intensity on the LCD. The test results of all layout circuits are functioning properly, and the measurement results can appear on the 16x2 I2C LCD.